2015
DOI: 10.3892/or.2015.4040
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell leukemia-1 promotes epithelial-mesenchymal transition of human gastric cancer cells

Abstract: Epithelial-mesenchymal transition (EMT) is a critical process that occurs during cancer progression, and cancer stem cells have been shown to acquire the EMT phenotype. Myeloid cell leukemia-1 (Mcl-1) has been implicated in cancer progression and is overexpressed in a variety of human cancers. However, the interaction between Mcl-1 and EMT in human gastric cancer (GC) is unclear. We investigated the impact of Mcl-1 expression levels on EMT and the underlying signaling pathways in human GC cells. We used the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Due to short half‐life and the possibility of having different post‐translational modifications, MCL‐1 has also been proposed to be a molecular timer for integration of different signaling outputs . Other than these attained roles of MCL‐1, this antiapoptotic BCL‐2 family member was shown to be involved in cell proliferation, autophagy, necroptosis, and epithelial–mesenchymal transition . Overall, each of these biological mechanisms should be investigated when inhibiting MCL‐1 so that inhibition toward MCL1‐1 is maintained without any undesirable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Due to short half‐life and the possibility of having different post‐translational modifications, MCL‐1 has also been proposed to be a molecular timer for integration of different signaling outputs . Other than these attained roles of MCL‐1, this antiapoptotic BCL‐2 family member was shown to be involved in cell proliferation, autophagy, necroptosis, and epithelial–mesenchymal transition . Overall, each of these biological mechanisms should be investigated when inhibiting MCL‐1 so that inhibition toward MCL1‐1 is maintained without any undesirable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…14 The expression of Mcl-1 has been shown to contribute to the metastatic capacity of tumor cells through promotion of EMT. 15 In this study, the regulation between miR-105 and Mcl-1 was studied to test Figure 4A show that the messenger RNA and protein levels of Mcl-1 were both upregulated in the miR-105 mimic group, while they were downregulated in the miR-105 inhibitor group, indicating Mcl-1 was positively regulated by miR-105. Next, the expression levels of Mcl-1 in A549 and Calu-3 cells were overexpressed and suppressed by transfection, and the changes in cell viability, migration, and EMT process were reassessed.…”
Section: Mir-105 Upregulated Mcl-1 To Promote the Viability Migratmentioning
confidence: 96%
“…As for p38, it has been reported that p38 activity and the expression of CD133 may have correlation in cancer stem cells originating from lung cancer, melanoma and liver cancer (Erdogan et al, ; Kumar et al, ; Wang et al, ; Yang et al, ; Zhao, Jia, Han, & Zhang, ). Furthermore, it has been shown that inhibition of p38 kinase activity suppressed cancer stem cell characteristics such as migration, infiltration and anchorage‐independent growth (Lee et al, ). However, enhanced activation of p38 in cancer stem cells of colon cancer, rhabdomyosarcoma and melanoma was found to stimulate cell death (Boothello et al, ; Ciccarelli et al, ; El‐Khattouti et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…of p38 kinase activity suppressed cancer stem cell characteristics such as migration, infiltration and anchorage-independent growth (Lee et al, 2015). However, enhanced activation of p38 in cancer stem cells of colon cancer, rhabdomyosarcoma and melanoma was found to stimulate cell death (Boothello et al, 2019;Ciccarelli et al, 2016;El-Khattouti et al, 2015).…”
Section: F I G U R E 4 Atp Synthesis Activity In Gpd2-knockdownmentioning
confidence: 97%